2018
DOI: 10.1111/cob.12260
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of artificial sweetened beverages associated with adiposity and increasing HbA1c in Hispanic youth

Abstract: SummaryResearch examining the impact of artificial sweetened beverages (ASBs) on obesity and metabolic diseases in adolescents is limited. The overall goal is to examine the longitudinal effects of ASBs on changes in adiposity and metabolic parameters in Hispanic adolescents. Longitudinal cohort with 98 Hispanics (12–18 years) who were overweight or had obesity with the following data at baseline and 1‐year later: anthropometrics, diet (24‐h recalls), body composition (DXA), glucose and insulin dynamics (oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We also found a statistically significant increase in HbA1c after consumption for 10 weeks of 96 mg sucralose. Davis et al also reported an increase in HbA1c in Hispanic young individuals with overweight or obesity who were frequent consumers of beverages with NNS at least for 1 year [28]. This effect could also depend on the diet content, for instance, sucralose consumption (≥5 days) in combination with an imbalanced diet has been shown to trigger a neuronal response which stimulates food intake in a fruit fly model [29]; nevertheless, in the present study no significant differences were found in the intake of macronutrients in any of the groups before and after the intervention for 10 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…We also found a statistically significant increase in HbA1c after consumption for 10 weeks of 96 mg sucralose. Davis et al also reported an increase in HbA1c in Hispanic young individuals with overweight or obesity who were frequent consumers of beverages with NNS at least for 1 year [28]. This effect could also depend on the diet content, for instance, sucralose consumption (≥5 days) in combination with an imbalanced diet has been shown to trigger a neuronal response which stimulates food intake in a fruit fly model [29]; nevertheless, in the present study no significant differences were found in the intake of macronutrients in any of the groups before and after the intervention for 10 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…33,116 One study with an analytic sample size less than 100 participants found no association between diet soda intake from 3-5 years of age with waist circumference at 5-6 years of age, 33 and one study with a sample size less than 1000 found no association with changes in percent body fat in adolscents. 116 Davis et al 143 found a significant association between LNCSB intake and increased total body fat levels in Hispanic adolescents with overweight or obesity, but no significant association with trunk fat or body fat percentage. Hasnain et al 27 found that greater unsweetened/diet beverage intake at 3-5 years of age was associated with greater cumulative sum of skinfolds at 15-17 years of age; however, they did not report effect magnitude and did not find a significant association with body fat percentage.…”
Section: Evidence Synthesismentioning
confidence: 99%
“… 37 studies identified through literature search from January 2000 to June 2019 were included in this systematic review, which examined the relationship between low and nocalorie sweetened beverages (LNCSB) and outcomes related to growth, size, body composition, and risk of overweight and obesity. 1,2,7,9,11,15,22,26,27,33,[41][42][43]46,55,62,68,103,104,106,116,118,119,127,131,137,[142][143][144][145][146][147][148][149][150][151][152] o Of the 17 papers in children, all were prospective cohort studies. o Of the 20 papers in adults, 6 were from RCTs and 14 were from prospective cohort studies.…”
Section: Summary Of the Evidencementioning
confidence: 99%
See 2 more Smart Citations